Drp-1 as Potential Therapeutic Target for Lipopolysaccharide-Induced Vascular Hyperpermeability - Luo, Xu (Oxid Med Cell Longev, 2020)
Mitochondria-dependent apoptotic signaling has a critical role in the pathogenesis of vascular hyperpermeability (VH). Dynamin-related protein-1- (Drp-1-) mediated mitochondrial fission plays an important role in mitochondrial homeostasis. In the present study, we studied the involvement of Drp-1 in resistance to VH induced by lipopolysaccharide (LPS). To establish the model of LPS-induced VH, LPS at 15 mg/kg was injected into rats in vivo and rat pulmonary microvascular endothelial cells were exposed to 500 ng/ml LPS in vitro. We found that depletion of Drp-1 remarkedly exacerbated the mitochondria-dependent apoptosis induced by LPS, as evidenced by reduced apoptosis, mitochondrial membrane potential (MMP) depolarization, and activation of caspase-3 and caspase-9. Increased FITC-dextran flux indicated endothelial barrier disruption. In addition, overexpression of Drp-1 prevented LPS-induced endothelial hyperpermeability and upregulated mitophagy, as evidenced by the loss of mitochondrial mass and increased PINK1 expression and mitochondrial Parkin. However, the mitophagy inhibitor, 3-Methyladenine, blocked these protective effects of Drp-1. Furthermore, inhibition of Drp-1 using mitochondrial division inhibitor 1 markedly inhibited LPS-induced mitophagy and aggravated LPS-induced VH, as shown by increased FITC-dextran extravasation. These findings implied that Drp-1 strengthens resistance to mitochondria-dependent apoptosis by regulating mitophagy, suggesting Drp-1 as a possible therapeutic target in LPS-induced VH.